The unity of understanding: A study of Kantian problems - Schwyzer, Hubert (Oxford Clarendon Press, 1990)
This is an analysis of Kant's account of human understanding--of our capacity to form concepts of, and to be conscious of, things in the world. Schwyzer argues that the conditions which Kant sets forth for understanding--conditions about the autonomy of thought, and about the relation of concepts to objects and of language to experience--cannot be satisfied within his overall picture of understanding as representing something to oneself. If Kant's conditions are to be satisfied, Schwyzer argues, understanding must be seen not as a capacity for mental representation, but as a capacity for action.